Imaging characteristics of renal epithelioid angiomyolipoma and its correlation with risk stratification - Jin Zhou; Guo-chu Qin; Ting-ting Chen; Le Cheng; Li Zhu (Scientific Reports)
Abstract Renal epithelioid angiomyolipoma (EAML) is frequently misdiagnosed due to nonspecific imaging findings. This study aimed to explore the radiographic characteristics of EAML, with the goal of enhancing the accuracy of preoperative diagnoses. A total of 27 patients with histopathologically confirmed renal EAML were included in the study. We retrospectively reviewed the radiographic features and analyzed the differences between tumors with a cut-off diameter of 40 mm. The majority of the lesions were isolated (25/27, 92.59%) and were predominantly found in females (18/27, 66.67%). ‌CT images revealed that most lesions were hyperdense, with fat detected in 13 cases. Small lesions were more likely to exhibit rapid wash-in and wash-out enhancement (p = 0.04), whereas abnormal vessels were more commonly found in large lesions. Tumors with higher risk stratification tended to show persistent or delayed enhancement on CT images. The imaging manifestations of renal EAML are diverse. After enhancement, small lesions are more likely to display rapid wash-in and wash-out patterns on CT images, whereas large lesions are more likely to exhibit abnormal vessels within or surrounding the tumor.